Knowledge, attitude, practice and compliance to weekly iron supplementation among female public junior high school students in West Papua - Isnaini, Yuni Subhi; Pihahey, Priscilla Jessica; Bahra, Bahra; Mintaningtyas, Sestu Iriami; Simanjuntak, Melicha Kristine; Fabanjo, Ivonne Junita (YCAB Publisher, 2024)
Background:Research indicates that the total iron intake among female adolescents aged 10–12 years who experience anemia is approximately 5.4 mg/day, significantly lower than the recommended daily requirement of 20 mg/day according to the 2013 Indonesian Nutritional Guidelines (AKG). To address this issue, the Indonesian government has implemented the Pemberian Tablet Tambah Darah pada Remaja Putri(PPAGB) program, which involves administering one iron tablet weekly over 12 months. However, the program's effectiveness is hindered by insufficient awareness of anemia's consequences and resistance among adolescents to consume iron tablets regularly. Objective:This study aimed to examine the association between female students' knowledge, attitudes, and practices (KAP) and their adherence to consuming iron supplements at Public Junior High School 08 Prafi, Manokwari, Papua. Methods:A school-based cross-sectional study was conducted between August and November 2023 among adolescent girls. A total of 226 participants were enrolled, divided into two phases: 75 participants in the first phase and 151 in the second. Weekly supplementation was provided for 12 weeks using 60 mg iron tablets. Data were analyzed using univariate, bivariate, and multivariable logistic regression analyses with SPSS version 27 to determine significant associations between adherence to iron tablet consumption and related variables at a significance level of p < 0.05. Results:Multivariate logistic regression analysis identified that accurate knowledge (OR = 0.403; p < 0.05), positive attitudes (OR = 0.226; p < 0.001), and frequent best practices (OR = 0.449; p < 0.05) were significantly associated with higher adherence to iron tablet consumption among female students. Conclusion:The findings suggest that enhancing female students' knowledge, attitudes, and practices regarding anemia and iron supplementation is crucial for improving adherence to iron tablet programs. Effective interventions should include educational initiatives to raise awareness about anemia and its consequences, alongside strategies to promote positive health behaviors. Keywords:knowledge; attitude; practice; compliance; iron supplements; anemia; Papua; Indonesia